Takba and the changing custom history of Northern Sagada, Mountain Province 1930-present - Punhalban, Jofalyn M. (2014., 2014)
The purpose of the study is to explore the changes and continuities in the role of takba in the community of Northern Sagada, Mountain Province. The takba, as a sacred basket, is used as a tool and material representation of the beliefs and practices in terms of healing and maintenance of wellness. Through oral history, this study identified the introduction of Christianity, education, market and new technologies as essential in the changes that happened in the role of the takba. Fear and the presence of elders as holders of traditional knowledge at the same time are identified as factors for the takba's continuing practice in the community. The factors that led to the changes further weakened the significance of the takba while the factors for the continuing role of takba helped in the survival of the material as well as the beliefs and practices surrounding it. From a normal basket used for the purpose of utility, the sangi and alyer on the oppigan,acquired a different usage in the culture of Northern Sagada as sacred basketor takba. It is now an item for ritual purposes.
The takba was originally nade as tool where the people can place their offerings to their relatives killed during the head taking period. Cultural change being inevitable led to the changing role of takba as a tool for traditional healing and wellness for the members of the clan taking care of it.
Thesis (Bachelor of Arts in Social Sciences)--University of the Philippines Baguio, 2014.
Includes bibliographical references (leaves 64-66).